Review paperPreclinical and clinical evidence of nephro- and cardiovascular protective effects of glycosaminoglycans - Cicero, Arrigo F.; Ertek, Sibel (Archives of Medical Science, 2010)
Despite advances in pharmacological treatment, diabetic nephropathy is still the leading cause of end-stage renal disease and an important cause of morbidity and mortality in diabetics. Glycosaminoglycans are long, unbranched mucopolysaccharides that play an important role in establishing a charge-selective barrier that restricts the passage of negatively charged molecules, such as albumin and other proteins, at the level of the glomerular basal membrane. Their loss is associated with loss of selectivity and proteinuria. Extensive preclinical evidence and some clinical trials suggest that glycosaminoglycans replacement is associated with improvement of glomerular selectivity and of proteinuria. Sulodexide could also have some other effects, potentially useful to reduce the renal damage and the cardiovascular disease associated with proteinuria, such as improvement of haemorheological and blood lipid parameters, an endothelium protective effect and anti-inflammatory action. This review will discuss the evidence supporting the potential nephroprotective effects of sulodexide and other glycosaminoglycans.